Learn GitHub flavored markdown - Dennison, Justin; Boose, Cherokee; Bryan, Wes (Packt Publishing, 2024)
Unlock the power of GitHub-Flavored Markdown with this comprehensive course, designed to simplify and enhance your documentation process. This series begins with an overview of Markdown, highlighting its advantages over other markup languages like HTML. You'll learn what GitHub-Flavored Markdown is and how it simplifies formatting tasks for better structure and styling. The initial episodes guide you through setting up your environment to write Markdown files with immediate rendering feedback, ensuring a smooth start. You'll master basic text formatting, including italicizing, bolding, and striking through text, as well as creating external and internal links. As you progress, you'll explore advanced formatting techniques, such as creating different heading sizes, blockquotes, and underlined headings. Practical demonstrations will teach you how to create lists, add images, and create images with links. In the advanced sections, you'll learn to leverage GitHub-Flavored Markdown's unique features. You'll arrange information in tables, inline code, create code blocks, and build task lists to keep track of your to-dos. By the end of this course, you'll be proficient in using GitHub-Flavored Markdown to enhance your documentation, making it more readable and professional.
Online resource; title from title details screen (O'Reilly, viewed June 24, 2024)
Keywords: Git (Computer file); Computer software -- Development; HTML (Document markup language); HTML (Langage de balisage); HTML; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet